MODIFIKASI REM TROMOL PADA YAMAHA JUPITER Z MENJADI REM CAKRAM DENGAN APLIKASI TEKNOLOGI CBS (COMBI BRAKE SYSTEM) - Anam, Khoirul; Triswanto, Juweni (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2017)
ABSTRACT Final project aims to improve the function of brake s in older to provide a level of confort and stability for the rider when braking. For those reasons need to modify drum brakes becames discs on a Yamaha Jupiter Z and apply the technologies CBS (Combi Btake System).Modifications process is among other that, changing the drum brake in to brake discs on the rear brake started by making holes for maunting the discs, the maufacture of the base master rear brakes , changing the lever swinging rear brake, the installation disk, the installaton of brake caliper rear, installation of brake hose, filling brake fluid, and bleeding process. This was followed b y applying technologies in to CBS (Combi Brake System) statrting changing the bolt dealer flurida on the master brake front, installation master clutch as a driving motion of the master flurida front towards the rear brake lever, replacing the hose on the front master and clutch master, and bleeding process.Overal brake performance testing can be done by means of a road test, a variable that is visible is the braking distance at varying speedsKeywords: disk brake, modification, test, Yamaha Jupiter Z.